1997
DOI: 10.1016/s1384-1076(97)00008-0
|View full text |Cite
|
Sign up to set email alerts
|

Eta Carinae: a long period binary?

Abstract: We present new observations of 71 Carinae, strongly suggesting that it is a binary system. High dispersion measurements of the broad Pay emission line show periodic radial velocity variations that are nicely explained by a star in a highly eccentric orbit. Velocity characteristics of the system imply massive components, in accord with the luminosity and spectral characteristics. Strong and variable wind-wind interactions are predicted to take place in v Car on the basis of the orbital elements and physical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
179
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(187 citation statements)
references
References 21 publications
8
179
0
Order By: Relevance
“…Damineli (1996) first noted a 5.5 yr period in the variability of the He I 10830Å line. Further photometric and radial velocity studies (Damineli et al 1997(Damineli et al , 2000, X-ray observations (Tsuboi et al 1997;Corcoran et al 2000 and references therein), and radio data (Duncan et al 1995(Duncan et al , 1999 have supported the 5.5 yr period and the binary hypothesis. However, the ground based radial velocity curve was not confirmed by higher resolution spectra with STIS, indicating that at least the time of periastron passage is not well defined by the UV and optical spectra (Corcoran et al 2001a).…”
Section: Introductionmentioning
confidence: 88%
“…Damineli (1996) first noted a 5.5 yr period in the variability of the He I 10830Å line. Further photometric and radial velocity studies (Damineli et al 1997(Damineli et al , 2000, X-ray observations (Tsuboi et al 1997;Corcoran et al 2000 and references therein), and radio data (Duncan et al 1995(Duncan et al , 1999 have supported the 5.5 yr period and the binary hypothesis. However, the ground based radial velocity curve was not confirmed by higher resolution spectra with STIS, indicating that at least the time of periastron passage is not well defined by the UV and optical spectra (Corcoran et al 2001a).…”
Section: Introductionmentioning
confidence: 88%
“…The "spectroscopic events", the X-ray observations and the spectroscopy suggest a colliding-wind binary (Damineli et al 1997(Damineli et al , 2000Pittard 2000). Another indication that η Car hides a secret is based on the detection of peculiar light variations of non-stellar origin, sometimes only clearly present in the near-UV, sometimes also detectable in V and B and deviating from the normal SD-variability.…”
Section: The Present Status Of η Carmentioning
confidence: 99%
“…The justification of serious doubt on the radial velocity curve of Damineli et al (1997) is certainly not new: two years before the study of Davidson et al (2000), de Groot & Henderson (1998, quoted by van Genderen et al 1999) already expressed their serious concern. They found that the HeI 5875Å and 6678Å lines (presumably originating deeper in the wind) gave radial velocities completely different from those on which the excisting binary models were based.…”
Section: The Present Status Of η Carmentioning
confidence: 99%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%